2013
DOI: 10.3928/01484834-20130328-03
|View full text |Cite
|
Sign up to set email alerts
|

Radiant Thinking and the Use of the Mind Map in Nurse Practitioner Education

Abstract: The concept of radiant thinking, which led to the concept of mind mapping, promotes all aspects of the brain working in synergy, with thought beginning from a central point. The mind map, which is a graphical technique to improve creative thinking and knowledge attainment, utilizes colors, images, codes, and dimensions to amplify and enhance key ideas. This technique augments the visualization of relationships and links between concepts, which aids in information acquisition, data retention, and overall compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…The use of mind mapping in nurse practitioner education supports enhanced memorisation of concepts. It was found that mind maps are creative ways for students to engage in a unique method of learning that can expand memory recall of key topics and help create a new environment for processing information (Spencer, Anderson, & Ellis, 2013).…”
Section: Mind Mappingmentioning
confidence: 99%
“…The use of mind mapping in nurse practitioner education supports enhanced memorisation of concepts. It was found that mind maps are creative ways for students to engage in a unique method of learning that can expand memory recall of key topics and help create a new environment for processing information (Spencer, Anderson, & Ellis, 2013).…”
Section: Mind Mappingmentioning
confidence: 99%
“…As for the facilitation and conversion of information into memory, it consists of spider diagrams, colour, pictures, keywords, association line, and highlighting key branches within a boundary known as 'chunking' (Howe, 1970;Bellezza, 1983;Day and Bellezza, 1983;Glass and Holyoak, 1986). This technique augments the visualisation of relationships and links between concepts, which aids in information acquisition, data retention, and comprehension (Spencer, Anderson and Ellis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Visualization with the form of creating mental images is a fundamental cognitive process which has been proved that it can improve students learning. Mind map is an excellent way to do this [10,11]. When a course chapter was finished, we ask the students to transcribe the content of this chapter into a mind map.…”
Section: After Classmentioning
confidence: 99%